Work in a warming world (Montreal, 2015)
"Global warming is perhaps the greatest challenge facing the twenty-first century. Environmental polices on the one hand, and economic and labour market polices on the other, often exist in separate silos creating a dilemma that Work in a Warming World confronts. The world of work - goods, services, and resources - produces most of the greenhouse gases created by human activity. In engaging essays, contributors demonstrate how the world of work and the labour movement need to become involved in the struggle to slow global warming, and the ways in which environmental and economic policies need to be linked dynamically in order to effect positive change. Addressing the dichotomy of competing public policies in a Canadian context, Work in a Warming World presents ways of creating an effective response to global warming and key building blocks toward a national climate strategy."